Evaluating microevolutionary models for the early settlement of the New World: The importance of recurrent gene flow with Asia - de Azevedo, Soledad (2011)
Different scenarios attempting to describe the initial phases of the human dispersal from Asia into the New World have been proposed during the last two decades. However, some aspects concerning the population affinities among early and modern Asians and Native Americans remain controversial. Specifically, contradictory views based mainly on partial evidence such as skull morphology or molecular genetics have led to hypotheses such as the "Two Waves/Components" and "Single Wave" or "Out of Beringia" model, respectively. Alternatively, an integrative scenario considering both morphological and molecular variation has been proposed and named as the "Recurrent Gene Flow" hypothesis. This scenario considers a single origin for all the Native Americans, and local, within-continent evolution plus the persistence of contact among Circum-Arctic groups. Here we analyze 2D geometric morphometric data to evaluate the associations between observed craniometric distance matrix and different geographic design matrices reflecting distinct scenarios for the peopling of the New World using basic and partial Mantel tests. Additionally, we calculated the rate of morphological differentiation between Early and Late American samples under the different settlement scenarios and compared our findings to the predicted morphological differentiation under neutral conditions. Also, we incorporated in our analyses some variants of the classical Single Wave and Two Waves models as well as the Recurrent Gene Flow model. Our results suggest a better explanatory performance of the Recurrent Gene Flow model, and provide additional insights concerning affinities among Asian and Native American Circum-Arctic groups.